2008
DOI: 10.1029/2007jb005454
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of slip‐weakening frictional laws with static restrengthening and their implications on the scaling, asymmetry, and mode of dynamic rupture on homogeneous and bimaterial interfaces

Abstract: [1] Dynamic simulations of homogeneous, heterogeneous and bimaterial fault rupture using modified slip-weakening frictional laws with static restrengthening are presented giving rise to both crack-like and pulse-like rupture. We demonstrate that pulse-like rupture is possible by making a modification of classical slip-weakening friction to include static restrengthening. We employ various slip-weakening frictional laws to examine their effect on the resulting earthquake rupture speed, size and mode. More compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 65 publications
3
42
0
Order By: Relevance
“…A fractal distribution for μ s along the fault was employed to investigate the effect of heterogeneities along the fault (Olsen-Kettle et al 2008;Olsen-Kettle & Mühlhaus in press). The dynamic coefficient of friction was proportional to μ s , where μ d = α μ μ s and α μ ranged from 0.6 to 0.75.…”
Section: Numerical Results For Earthquake Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A fractal distribution for μ s along the fault was employed to investigate the effect of heterogeneities along the fault (Olsen-Kettle et al 2008;Olsen-Kettle & Mühlhaus in press). The dynamic coefficient of friction was proportional to μ s , where μ d = α μ μ s and α μ ranged from 0.6 to 0.75.…”
Section: Numerical Results For Earthquake Modelmentioning
confidence: 99%
“…F n and F τ are normal and tangential restoring forces at the fault interface given by the penalty method to prevent slip from occurring. The elastic wave equation was solved using the finite-element method (Olsen-Kettle et al 2008).…”
Section: Numerical Results For Earthquake Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…MESH DEPENDENCE AND SLIP COMPLEXITY 1663 modified slip-weakening model when a point on the fault is no longer slipping inelastically [12]. Both pulse-like and crack-like rupture can be produced since the fault can re-strengthen to its initial static value of friction after rupture.…”
Section: Mesh Dependence and Slip Complexitymentioning
confidence: 98%
“…Olsen-Kettle et al (2008) showed that this greatly reduces the mesh-dependency associated with the ill-posedness in the sense of Renardy (1992).…”
Section: Friction Lawmentioning
confidence: 99%